Organizational ethnography between toolbox and world-making - Yanow, Dvora (Journal of organizational ethnography, 2012)
Purpose - The purpose of this paper is to take account of organizational ethnography in its historical and methodological context, on the occasion of the inauguration of the Journal of Organizational Ethnography.Design methodology approach - This essay brings together some current issues and concerns in one form of "marked" ethnography.Findings - This essay touches on the questions: what is organizational ethnography and why is it re-emerging now?; and on related questions, on its way to engaging some of the key methodological issues in organizational ethnography that today merit attention.Originality value - The paper may be of value to readers who are interested in the method and in one researcher's conceptual-methodological take on it.